Original paper Cutaneous myiasis in patients returning from tropical regions: a case reports - Waśniowski, Aleksander; Rehlis, Norbert (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2006)
Following the rising numbers of visitors to tropical countries each year, some specific medical conditions appear connected with hot climate and poor sanitation in the developing regions of the world, resulting in an increase in the number of tropical disease cases. This fact makes physicians take the patient’s medical history as well as travel history, especially in the case of untypical, difficult to explain skin lesions. Myiases in man are rarely diagnosed parasitoses, which are usually associated with extreme lack of hygiene or invasion of necrotic tissues in moderate climate. In tropics, however, there are many species of arthropods using vertebrates (including humans) as intermediate hosts necessary to close their life cycle. In some, rare cases myiasis may be fatal, but almost always have a strong, negative psychological impact to the patient. We reported two cases of cutaneous myiases in Polish travellers, caused by species typical of the Old and New World tropical areas, diagnosed and treated in the Department and Clinic of Tropical and Parasitic Diseases in Poznań